Analyzing the Prevalence of the Eight Focus Crimes in Albay Province: Basis for Sustainable Crime Prevention Framework - Pabelonia, Dennis; Macabeo, Manny (JPAIR Multidisciplinary Research, 2026)
The prevalence of crimes globally is a complex and varied phenomenon, with different regions and countries experiencing vastly unequal rates across various types of offenses. To prevent these, the Philippine legal system addresses criminality primarily through two main bodies of law: the Revised Penal Code, which defines traditional crimes that target modern offenses. This study determined the statistical profile of Eight Focus Crime in the province of Albay, analyzed the prevalence, identify the problems encountered and propose an Sustainable Crime Prevention Framework that will suppress the commission of Eight Focus Crimes. This study was conducted in the province of Albay, specifically in the Legazpi, Ligao and Tabaco City, covering the period from CY 2022 to 2024. This study used the descriptive qualitative method research design. The respondents of the study are Intelligence, Investigators, Operations and PCAD personnel from the three CPS. The study reveals that Albay’s crime landscape is a structural byproduct of socio-economic strain and geographic isolation, where policing deserts and seasonal economic droughts sustain a cycle of survivalist criminal behavior. Data confirms that while Legazpi City remains the urban epicenter for property crimes, a critical shift toward lethal violence has emerged in jurisdictions like Ligao, requiring a move from reactive enforcement to multi-sectoral, restorative justice.
Keywords: Social Science; Analysis; Prevalence; Eight Focus Crimes; Sustainable Crime Prevention Framework